Business Strategy To Increase Company Profit: Leveraging New Business Model CRO (Contract Research Organization) At Laboratory Animal Division PT. XYZ - Rafiqi, Bagus; Mulyono, Nur Budi; Maharani, Maharani (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The increasing prevalence of infectious and non-communicable diseases has spurred pharmaceutical and biotechnology companies to intensify research and development efforts for new drugs, particularly vaccines. The COVID-19 pandemic has prompted many companies and research institutions to find solutions. Preclinical testing in animals is mandatory in vaccine development, which highlights the importance of animals to ensure the safety and efficacy of drugs before clinical trials (conducted in humans). The surge in demand for animal testing presents a unique opportunity for PT XYZ to leverage the Laboratory Animal Division (LAD) as a Contract Research Organization (CRO). By offering services such as providing laboratory animals, providing materials of animal origin, and facilitating testing, PT XYZ transformed DHL from a cost center to a profit center. This research aims to identify customer needs and evaluate the business potential of CRO in DHL PT XYZ. This study combines qualitative data analysis with the Kepner Tregoe method and quantitative with the Analytical Hierarchy Process (AHP) method. This study recommends that PT XYZ prioritize the implementation of strategies aimed at improving service quality, expanding the variety of animal breeds and services, and obtaining relevant certifications. The results of this analysis and business strategy cost leadership are essential to increase customer satisfaction, grow market share, and ultimately achieve the company's revenue growth target.